2017
DOI: 10.1186/s13014-017-0829-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of local-regional recurrence after conformal and intensity-modulated radiotherapy for head and neck cancer

Abstract: AimTo evaluate the patterns of loco-regional recurrences in head and neck cancer patientsMethodsTwenty-six out of 112 patients treated with primary or postoperative 3D CRT or IMRT for their primary and recurrent disease between 2007 and 2013 were included. The CT images of recurrent disease were rigidly registered with the primary CT images for each patient. To assess overlaps and overlap localization, the recurrence volume overlapping with the primary target volume was identified. For relapses occurring in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Although half of our patients who had an in-field recurrence had received definitive CRT as a primary treatment, no significant relation was observed between primary treatment modality and recurrence class. This result is similar to the findings of Johansen et al [16] who did not include information about p16 status in their findings but based on tumor sites included mostly p16 negative patients.…”
Section: Treatmentsupporting
confidence: 91%
“…Although half of our patients who had an in-field recurrence had received definitive CRT as a primary treatment, no significant relation was observed between primary treatment modality and recurrence class. This result is similar to the findings of Johansen et al [16] who did not include information about p16 status in their findings but based on tumor sites included mostly p16 negative patients.…”
Section: Treatmentsupporting
confidence: 91%
“…Prior works have documented the different failure patterns for HNC patients. Oksuz et al (8) and Johansen et al (7), for example, analyzed the recurrence patterns among HNC patients treated with radical (chemo-) radiotherapy. They reported that “in field” failures were the majority of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is a particular therapeutic method for haematological neoplasms (Johansen et al, 2017). A combination of melatonin with 4 Gy irradiation induced apoptosis of Jurkat leukaemia cells in C57BL/6 mice, concomitant with prolonged lifetime of the leukaemic animals.…”
Section: Figurementioning
confidence: 99%